A Modern Approach to Preventing Prosthetic Joint Infections - Papas, Paraskevi Vivian; Congiusta, Dominick; Scuderi, Giles R.; Cushner, Fred D. (The Journal of Knee Surgery, 2018)
Total knee arthroplasty (TKA) is recognized as one of the most successful surgical procedures performed today. One of the most common and dreaded complications of TKA is postoperative infection. To prevent infections, it is critical to identify patients at high risk through analyzing their risk factors, and help in addressing them prior to surgery. The effort to prevent infection must be carried through every step of the surgical process, from preoperative counseling to intraoperative measures and postoperative protocols. Hair removal, the application of antiseptics, the utilization of antibiotics, barbed sutures, smart dressings, and antibacterial washes are some of the avenues surgeons may explore to help prevent infection.
Keywords: total knee arthroplasty; infection; barbed sutures; smart dressing